Reforming Fiscal and Economic Management in Afghanistan - Carnahan, Michael; Manning, Nick; Bontjer, Richard; Guimbert, Stéphane (Washington, DC: World Bank, 2013)
The paper cover two broad themes in the recent reform of fiscal and economic management in Afghanistan. The first part, The Journey So Far, sets out the impressive policy and institutional reforms that the Interim and Transitional Administrations have made since the Bonn conference in November 2001. It provides some details of the challenges faced by the Ministry of Finance, and very particularly the complexities of managing intensive donor interest and significant volumes of development assistance, while balancing the need for responsiveness to donor priorities with a concern to build institutional strengths of the public sector. The section notes the complexity of the vested interests that had built up within the administration during the Soviet and Taliban periods, and the need to revive, while simultaneously reforming, the fiscal management processes. The second part, Current Priorities, explores the fiscal and economic management tasks that the Ministry of Finance is now confronted with. The section opens with a review of the strategic options for structuring the Ministry of Finance, and the additional challenges and opportunities presented by the new constitution. The revised budget law is perhaps the most significant and far-reaching of the institutional reforms planned. The significance of the municipalities as a potential platform for enhanced service delivery to an increasingly urbanized population is also noted.